IMPACT OF ISRAELI-HAMAS WAR ON EDUCATION/LEARNING AND LEARNERS’ MENTAL HEALTH IN ISRAEL, GAZA STRIP AND THE USA: A SYSTEMATIC REVIEW OF LITERATURE - Josephine Oranga (RADJA PUBLIKA, 2024)
Educators hope that Israel and the Gaza Strip’s experience during the corona-virus pandemic will make the management of education and learning during the current Israeli-Hamas war a little easier as education systems grapple with trauma amongst teachers and learners, on both sides of the divide. It is not clear how long this situation will last, but it definitely means putting on hold the traditional scheduled educational programmes and progress, in most instances, in favour of online and hybrid make-shift educational programmes with the hope that normalcy returns soon. In times of crisis, ideally, the population of learners affected by the crisis need clear directives and frameworks coupled with caring and sensitive teachers and frequent in-person and hybrid meetings amongst teachers and learners to provide re-assurance and hope. Notably, the main dynamic during war is the learners’ constant fear of attacks to them or their families as uncertainty looms large. This fear leads to anxiety, thereby adversely impacting the learners’ mental well-being. This paper, thus, discusses educational situation with regard to Israel, Gaza and to a limited extent, the USA, in light of the latest Israeli–Hamas conflict that began on October the 7th, 2023, following a Hamas attack on Israeli civilians leading to retaliatory attacks from Israel. Accordingly, the main impacts of the war are disruption of education systems and structures, shift to remote learning, psychological trauma and insecurity and fear amongst learners.